2021
DOI: 10.1016/j.omto.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-detargeting proves more effective than leader gene deletion for improving safety of oncolytic Mengovirus in a nude mouse model

Abstract: A dual microRNA-detargeted oncolytic Mengovirus, vMC 24 NC, proved highly effective against a murine plasmacytoma in an immunocompetent syngeneic mouse model; however, there remains the concern of escape mutant development and the potential for toxicity in severely immunocompromised cancer patients when it is used as an oncolytic virus. Therefore, we sought to compare the safety and efficacy profiles of an attenuated Mengovirus containing a virulence gene deletion versus vMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“… 6 MC 24 -NC was previously reported to be a safe and relatively potent oncolytic virus, with varying efficacy depending on the tumor model. 6 , 7 , 8 For the purpose of the current study we generated two additional vectors carrying either a full deletion of the polyC tract (MC 0 -NC) or a long polyC tract (MC 37 -NC) with the sequence C 26 UC 10 ( Figure 2 A). The use of Mengovirus with a wild-type polyC length (C 44 UC 10 ) raises several safety concerns because of its zoonotic potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 MC 24 -NC was previously reported to be a safe and relatively potent oncolytic virus, with varying efficacy depending on the tumor model. 6 , 7 , 8 For the purpose of the current study we generated two additional vectors carrying either a full deletion of the polyC tract (MC 0 -NC) or a long polyC tract (MC 37 -NC) with the sequence C 26 UC 10 ( Figure 2 A). The use of Mengovirus with a wild-type polyC length (C 44 UC 10 ) raises several safety concerns because of its zoonotic potential.…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 4 , 5 Mengovirus MC 24 -NC, an attenuated and microRNA (miRNA)-detargeted picornavirus, was previously shown to be a safe and efficacious OV in a murine multiple myeloma model. 6 However, a consistently curative therapy with complete and durable response across multiple tumor models was not achieved, 7 , 8 which suggested that the virus may have been over-attenuated and that the therapeutic outcome might be improved if certain attenuating mutations were reversed.…”
Section: Introductionmentioning
confidence: 99%
“…vMC 24 NC was generated by the insertion of neuron- and cardiac/muscle-specific miRNA targets into the viral genome. The in vivo analysis of the syngeneic murine plasmacytoma model showed excellent therapeutic efficacy without significant virus-mediated toxicity [ 126 ]. Combining OVs and miRNAs showed reduced toxicity and enhanced potency in preclinical models.…”
Section: Oncolytic Virusesmentioning
confidence: 99%